Peningkatan Keterampilan SDM dalam Rangka Menunjang Program Destinasi Wisata Mina Politan - Siti Prihatiningtyas; Lukmanul Hakim; Uswatun Niswah; Ahmad Fatoni (Empower : Jurnal Pengembangan Masyarakat Islam, 2022)
The Covid-19 pandemic has increased problems related to the capacity of the Human Resources (HR) of the community around Sumurrejo Village, Semarang. Seeing the low quality of human resources "marginalized", then non-formal education plays an important role in honing skills. This study aims to explain the increase in human resources in implementing the Mina Politan Tourism destination program for MSMEs in Sumurrejo Village through eco print batik training. Research using descriptive qualitative method with interview techniques. The results of the research include an increase in human resources with increased life skills, natural coloring of batik, economic independence, local people who have attended training have a desire to be aware of being independent in the economy, especially in the development of human resources from millennials and the creation of batik communities in urban Sumurrejo Village.